2008
DOI: 10.1016/s0140-6736(08)60726-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ustekinumab, a human interleukin-12/23 monoclonal antibody, in patients with psoriasis: 52-week results from a randomised, double-blind, placebo-controlled trial (PHOENIX 2)

Abstract: Although treatment with ustekinumab every 12 weeks is effective for most patients with moderate-to-severe psoriasis, intensification of dosing to once every 8 weeks with ustekinumab 90 mg might be necessary to elicit a full response in patients who only partially respond to the initial regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
1,213
7
48

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,298 publications
(1,318 citation statements)
references
References 19 publications
50
1,213
7
48
Order By: Relevance
“…In all, 38 RCTs (identified in 38 reports)20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 met the eligibility criteria and were included, as shown in Figure 1. These trials involved a total of 18 024 patients with plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 38 RCTs (identified in 38 reports)20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 met the eligibility criteria and were included, as shown in Figure 1. These trials involved a total of 18 024 patients with plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in 27 RCTs20, 21, 22, 25, 27, 28, 29, 30, 31, 34, 35, 36, 37, 38, 39, 40, 43, 45, 46, 47, 48, 50, 52, 53, 57 did not experience MACEs while exposed to any interventions but 10 MACEs were observed during the randomized controlled phase of nine studies 23, 26, 32, 33, 42, 44, 49, 51. Overall, the pooled analysis of these nine trials found that there was no statistically significant difference in the risk of MACEs when comparing biologic therapies with placebo (pooled OR 1·45, 95% CI 0·34–6·24, P  = 0·62), as shown in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…Erythema (redness): diameter (mm) and severity from none to severe (0 = none, 1= mild, 2 = moderate 3 = severe) Swelling/Induration: diameter (mm) and severity from none to severe (0 = none, 1= mild, 2 = moderate 3 = severe) Hematoma: yes/ no and if present diameter (mm) Local pain -assessed by the study subject on a visual analogue scale (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) Refer to appendix K Pruritus -assessed by the study subject on a visual analogue scale (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) Refer to appendix L …”
Section: Local Tolerance and Tolerabilitymentioning
confidence: 99%
“…In 2014, the World Health Organisation recognized psoriasis as a serious non-communicable disease and its report from 2016 highlighted the life running nature of the disease and the need to urgently research and make accessible cost effective medicines throughout the world. 1 The development of monoclonal antibodies that target cytokines central to the psoriatic disease cascade including TNF, IL-23, and IL-17A, has significantly broadened the therapeutic armamentarium [2][3][4] however, recent surveys indicate restricted usage of these expensive therapies in less than 10% of patients with moderate-to-severe disease even in Western countries. 5 For over 50 year's methotrexate (MTX) has been used in the treatment of psoriasis and psoriatic arthritis and is recommended as first-line systemic agent for the treatment of moderate-to-severe psoriasis in US and European guidelines 6 mainly based on experience and health economic considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Results from these studies support that switching to ustekinumab is effective and well tolerated for most patients, given the high overall PASI 75 response rates at week 12 (67.1% with the 45‐mg dose in PHOENIX 1 and 66.7% with the 45‐mg dose in PHOENIX 2) and acceptable safety profile of ustekinumab 68, 69. Similarly, in the phase 3 ERASURE and FIXTURE studies of the IL‐17A antibody, secukinumab, 12.5–29.3% of patients had psoriasis that was poorly controlled with previous a biologic therapy (anti‐TNFα or ustekinumab), with up to 7.6% of patients experiencing no response to previous anti‐TNFα therapy 15.…”
Section: Published Literature Evaluating Switching Psoriasis Treatmentsmentioning
confidence: 64%